2014
DOI: 10.1186/1475-2875-13-247
|View full text |Cite
|
Sign up to set email alerts
|

Reports of long-lasting insecticidal bed nets catching on fire: a threat to bed net users and to successful malaria control?

Abstract: BackgroundOne of the control tools to reduce malaria transmission is the use of LLINs. However, several studies show that household bed net use is quite low. A study was developed to better understand the cultural factors that might explain these gaps in Benin. One reason mentioned is that bed nets can catch on fire and cause harm. This paper presents a summary of these findings, their analysis and the ensuing issues.MethodsThis anthropological study is based on an inductive qualitative approach, including 91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…The same trend was observed for the pregnant women. This confirms the report of the World Health Organization (WHO) [ 15 ], and Ergot et al [ 16 ] on the use of LLINs as a means to reduce the lethal impact of malaria. Malaria occurred at higher prevalence among non-users and this is in line with the works of Ergot et al [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same trend was observed for the pregnant women. This confirms the report of the World Health Organization (WHO) [ 15 ], and Ergot et al [ 16 ] on the use of LLINs as a means to reduce the lethal impact of malaria. Malaria occurred at higher prevalence among non-users and this is in line with the works of Ergot et al [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…This confirms the report of the World Health Organization (WHO) [ 15 ], and Ergot et al [ 16 ] on the use of LLINs as a means to reduce the lethal impact of malaria. Malaria occurred at higher prevalence among non-users and this is in line with the works of Ergot et al [ 16 ]. The prevalence of malaria in children was higher than that of pregnant women and this was probably because of the absence of protective immunity in the children and the fact that they could easily roll out of their LLINs at night without their guardians/parents noticing.…”
Section: Discussionsupporting
confidence: 89%
“…Factors such as age (<30 years), social status, the belief in the efficacy of bed nets and their accessibility and ownership of television and radio influenced the use of mosquito nets [ 46 48 ]. A recent anthropological study has showed that the inhabitants in one locality of Benin were not using their nets, because for them, nets can cause fires, since cases of mosquito-net related burns were recorded in this locality [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least one hole was observed in nearly 90% of the bed nets surveyed. This study resembles with the works of Ergot et al2 Also this study is consistent with the result of the study conducted by J.Pulfold et al…”
supporting
confidence: 93%